Efeito de uma dieta rica em sacarose no fígado de animais com cirrose hepática induzida por Tioacetamida - Silva, Bianca Sulzbacher da (2020)
Cirrhosis is considered one of the most common causes of death in the world and the main chronic liver disease. It is characterized by a change in the normal architecture of the liver, which is replaced by regenerative nodules, separated by fibrous tissue, usually accompanied by hepatocellular necrosis. Liver cirrhosis is considered a catabolic disease, whith muscle weakness, anorexia and weight loss Cirrhotic patients have a low energy intake and high energy expenditure at rest, leading to metabolic disorders and worsening of the clinical picture. Randomized studies have already shown that a nutrition al intervention with increase of energy in take significantly improves the survival of cirrhotic patients. Despite these clinical observations, few studies have verified the mechanisms involved and the effect of a high sugar diet in an animal model of liver cirrhosis. Therefore, our aim was to evaluate the effect of a high sugar diet in the liver of animals with liver cirrhosis induced by thioacetamide. For this, we used male Wistars rats, which were divided in to three groups: Control (C); Thioacetamide (TAA) and Thioacetamide + High sugar diet (TAA + HSD). Liver cirrhosis was induced by the administration of thioacetamide, a hepatotoxic drug, at a dose of 100mg kg-1 twice a week intraperitoneally (i.p) for 8 weeks. The sugar was offered in water (300g L-1) for 8 weeks. After the experimental period, the animals were submitted to the glucose tolerance test (GTT). After euthanizing the animals, liver histology experiments, serum biochemical analyzes of liver function, metabolism and liver oxidative stress were performed. The comparison bet ween groups was performed using the one-way ANOVA test followed by the Tukey test, orthe Kruskal-Wallis test followed by the Dunns post-test. The confidence level for the tests was 95%. According to our results, the administration of TAA modified the hepatic architecture, increased the fibrosis and inflammatory infiltrate observed in the histological analysis and promoted a increase in the levels of transaminases (ALT and AST). The high sugar diet promoted a reduction in fibrosis and liver inflammation in addition to ALT levels. Oxidative stress was observed by the increase in TBARS in the TAA group, which was reduced in animals of TAA + HSD group. The animals in the TAA group had reduced caloric intake, weight loss and body fats in addition to reduced hepatic glucose levels. These parameters were normalized in the animals of TAA + HSD group, which presented increased caloric intake and recovery from weight loss. Thus, the high sugar diet is efficient in improving liver cirrhosis, having anti-inflammatory and antioxidant effect, improvement of hepatic glucose metabolism and malnutrition state energy.